ANALISIS PERAN KETUA MASJID AL-IKHLAS SEBAGAI PIONIR DAKWAH DI MASYARAKAT DESA SEDANG KEC. SUAK TAPEH - Rahwana Rahwana; Hasril Atieq Pohan (Yonetim Jurnal, 2023)
This research entitled "Analysis of the Role of the Chairman of the Al-Ikhlas Mosque as a Da'wah Pioneer in the Community of Sedang Village, Suak Tapeh District" aims to determine the role of the chairman of the Al-Ikhlas Mosque as a missionary pioneer in the Sedang Village, Suak Tapeh District. This research uses a descriptive qualitative method, using a direct approach or going into the field to collect data and information related to the problem being studied, namely conducting interviews and observations. The object of this research is the head of the Al-Ikhlas mosque who is a pioneer of da'wah and is a liaison, leader and religious figure in the spread of Islam in Sedang Village, Suak Tapeh District as primary data and carries out observations and interviews with several sources such as mosque administrators and village communities as secondary data sources. Both primary data and secondary data were obtained through observation and in-depth interviews with six sources concerned. Based on the research results, it can be concluded that the role of the head of the Al-Ikhlas mosque as a pioneer of da'wah to the people of Sedang village, Suak Tapeh District is quite active, by implementing interpersonal roles, informational roles and decision-making roles. role) so that existing programs can be implemented well. However, the role as a da'wah pioneer, which consists of providing motivation, mentoring, building relationships, organizing communication and developing or improving da'wah implementers, is still minimal because many people are not involved in da'wah activities led by the head of the mosque and the quality of the mosque head's leadership skills in inspiring, motivating and leading the community in da'wah efforts is also lacking.